HUBUNGAN INTENSITAS AKSES MEDIA BARU DAN KUALITAS INTERAKSI LINGKUNGAN SEKITAR PADA MAHASISWA UNTAG SURABAYA - Norhabiba, Fitri; Ragil Putri, Sukma Ari (Master of Communication Science Program, Universitas Diponegoro, 2018)
The Internet has changed the way people communicate including how internet have used as the tools for producing and distributing the message. In Indonesia, the number of internet user has been increasing, particularly internet user who categorized as the youth. Some research states that the high internet user in this group has the correlation with the low quality of family interaction, the decrease of the social relationship as well as the feeling of lonely. This article tries to support those arguments. By applying the theory of Uses and Gratification and Computer-Mediated Communication (CMC) this article tries to understand the correlation between the intensity of new media access and the quality of interaction of the internet user to the surrounding environmental interaction. The population is a student of Untag Surabaya who representing urban youth. This research involved 388 samples that are taken by using systematic random sampling. The results of the study show that there is a relationship between the intensity of accessing new media to the quality of the surrounding environmental interaction. The test results show that there is positive, strong, and significant correlation r (388) = 0,759; and 0.759, p <0.05. The higher the intensity of new media access, the higher the interaction of the environment around the students. This study is expected to provide new insights and findings related to the quality of students' social interactions relating to the use of new media.